2013
DOI: 10.1021/bm301999c
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Initiated Ring-Opening Polymerization of O-Carboxyanhydrides for the Preparation of Anticancer Drug–Poly(O-carboxyanhydride) Nanoconjugates

Abstract: We report a novel synthetic strategy of polymer-drug conjugates for nanoparticulate drug delivery: hydroxyl-containing drug (e.g., camptothecin, paclitaxel, doxorubicin and docetaxel) can initiate controlled polymerization of phenyl O-carboxyanhydride (Phe-OCA) to afford drug-poly(Phe-OCA) conjugated nanoparticles, termed drug-PheLA nanoconjugates (NCs). Our new NCs have well-controlled physicochemical properties, including high drug loadings, quantitative drug loading efficiencies, controlled particle size wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 40 publications
3
94
0
Order By: Relevance
“…[44] The CCL micelles not only improved the structural stability but also allowed the controlled release of cargo molecules in response to the reducing reagent. [45,46] In this work, we developed a versatile method to prepared photo-responsive poly(α-hydroxy acids) with pendent o-NB ester group. The photolabile o-NB ester group was introduced into the side chain of the hydrophobic poly(α-hydroxy acids) via coppercatalyzed azide-alkyne cycloaddition (CuAAC) reaction between 2-nitrobenzyl 6-azidohexanoate and amphiphilic mPEG-b-Poly(-Tyr) (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…[44] The CCL micelles not only improved the structural stability but also allowed the controlled release of cargo molecules in response to the reducing reagent. [45,46] In this work, we developed a versatile method to prepared photo-responsive poly(α-hydroxy acids) with pendent o-NB ester group. The photolabile o-NB ester group was introduced into the side chain of the hydrophobic poly(α-hydroxy acids) via coppercatalyzed azide-alkyne cycloaddition (CuAAC) reaction between 2-nitrobenzyl 6-azidohexanoate and amphiphilic mPEG-b-Poly(-Tyr) (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Tong (Figure 3a), predefined drug loadings and controlled drug release kinetics (48,49). Nanoparticles with diameter range from 70nm to 200nm can be fabricated depending on different polymer-CPT ratio.…”
Section: Nanoparticles From Self-assembly Of Polymersmentioning
confidence: 99%
“…They prepared the drug-poly(Phe-OCA) conjugates (Cpt-PheLA n , where n is the degree of polymerization) by nanoprecipitation followed by self-assembly of Cpt-PheLA n conjugates in water to form nanoconjugates with well controlled physicochemical properties. They reported that poly(PheLA-OCA)-Cpt nanoconjugates exhibited 100% drug loading efficiency at PheLA-OCA/Cpt ratios of 25:1; 50:1 and 100:1 with narrow particle size distribution (100 -125 nm), sustained drug release profiles without 'burst' drug release, remarkable stability in human serum with negligible aggregation and controlled cytotoxicity compared with PLA nanoconjugates (225). In this case it is possible to predict the drug loading efficiency from the PheLA-OCA/Cpt ratio used during polymerization.…”
Section: Drug Loading Strategiesmentioning
confidence: 99%
“…Presently there is limited application of QbD principles to systematic development of nanoconjugates in literature. However in order to address these problems, many researchers have focused on ring opening polymerization (ROP) of lactide (LA) followed by nanoprecipitation of the resulting PLA-drug conjugate (223)(224)(225). The drug release from the nanoconjugate was tuned by controlled cleavage of the lactate ester bond between the drug and polymer by hydrolysis in the physiological solution.…”
Section: Quality By Design (Qbd) Principlesmentioning
confidence: 99%